Man-machine speech communication : 14th National Conference, NCMMSC 2017, Lianyungang, China, October 11-13, 2017, revised selected papers /: 14th National Conference, NCMMSC 2017, Lianyungang, China, October 11-13, 2017, revised selected papers. ([2018]) - Unknown
No abstract available